1986
DOI: 10.1073/pnas.83.10.3407
|View full text |Cite
|
Sign up to set email alerts
|

Tumor rejection antigens of chemically induced sarcomas of inbred mice.

Abstract: Chemically induced sarcomas of inbred mice are immunogenic in syngeneic hosts, and preimmunization with tumor cells leads to resistance to subsequent tumor transplants. The tumor rejection antigens (TRAs) that mediate this reaction are highly specific for each tumor; cross-protection between different syngeneic sarcomas is rare. Isolated membrane and cytosol fractions from two antigenically distinct BALB/c sarcomas, Meth A and CMS5, have TRA activity, and biochemical characterization of the active components f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
281
0
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 407 publications
(291 citation statements)
references
References 23 publications
8
281
0
2
Order By: Relevance
“…It has been demonstrated that inbred mice and rats immunised against their own tumours or tumours of the same genetic background become immune to challenges with tumour cells (Srivastava and Old, 1988 (Srivastava et al, 1986(Srivastava et al, , 1993Udono and Srivastava, 1993). However, it appears not to be the hsp itself that causes this immune response, rather the peptides that are attached to it.…”
Section: Hsp9omentioning
confidence: 99%
“…It has been demonstrated that inbred mice and rats immunised against their own tumours or tumours of the same genetic background become immune to challenges with tumour cells (Srivastava and Old, 1988 (Srivastava et al, 1986(Srivastava et al, , 1993Udono and Srivastava, 1993). However, it appears not to be the hsp itself that causes this immune response, rather the peptides that are attached to it.…”
Section: Hsp9omentioning
confidence: 99%
“…The first reports of an immunological role for heat shock proteins (HSPs) were published over two decades ago (Srivastava et al 1986;Ullrich et al 1986) where it was shown that isolated HSPs when used as an immunogen protected syngeneic mice from the same tumour challenge and induced tumour-specific immunity. Since then, it has been reported that HSPs, including heat shock protein 70 (HSPA), were effective in cross-priming CD8 + T cells against the tumour from which these chaperones were isolated, recently reviewed by Srivastava (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock proteins of 96-kDa size (gp96) have been suggested to mediate this antigenicity in the case of a number of methylcholanthrene-induced sarcomas (2-4) and a UV-induced fibrosarcoma (S. Janetzki, N. E. Blachere, and P.K.S., unpublished results). Administration of a purified gp% preparation renders mice resistant to the tumor from which gp% is isolated but not to an antigenically distinct tumor (2). In light of a lack of differences in the gp96 cDNA sequence among different tumors or among tumors and normal tissues, we suggested that the tumor-specific antigenicity of gp96 may derive not from gp96 per se but from low molecular weight peptides associated with gp% (5, 6).…”
mentioning
confidence: 99%
“…Purification of gp96. gp96 was purified from Meth A cells as described (2). Briefly, a 60-ml pellet of Meth A cells was lysed in 240 ml of hypotonic buffer (30 mM NaHCO3/0.5 mM phenylmethylsulfonyl fluoride, pH 7.1) by Dounce homogenization, and a 100,000 x g supernatant was obtained.…”
mentioning
confidence: 99%